Composite flour as an innovative food ingredient in bakery products: A review - Syaidahtull Naseha Ibrahim; MacDalyna Esther Ronie; Ahmad Hazim Abdul Aziz; Rovina Kobun; Wolyna Pindi; Fan Hui Yin; Jumardi Roslan; Norazlina Mohammad Ridhwan; Sylvester Mantihal; Mohd Khairi Zainol; Nicky Rahmana Putra; Hasmadi Mamat (International Journal of Food, 2025)
Composite flour, a widely utilised ingredient in food production, particularly in baking, offers an innovative approach to enhance the nutritional and technological properties of flour. This review was conducted to compare the quality attributes of various bakery products, including breads, biscuits, and cakes, produced using different types of composite flour. The review primarily focuses on evaluating the changes in physical, chemical, and sensory characteristics brought about by this composite flour in bakery products. Ultimately, the findings of the review reveal that composite flour significantly influences the textural properties, nutritional composition, and sensory acceptance of bakery products.